2012
DOI: 10.1590/s0004-27492012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between central subfield thickness, visual acuity and structural changes in diabetic macular edema

Abstract: Purpose: To correlate the central subfield thickness (CST) measured by Cirrus TM SD-OCT with best-corrected visual acuity (BCVA) and structural changes in diabetic macular edema (DME). Methods: The transversal study evaluated 200 patients with non-proliferative dia betic retinopathy (NPDR) and selected 55 eyes with DME between January, 2010 and April, 2011. Spectral domain OCT was performed in patients with type 2 diabetes and DME. CST and BCVA were correlated with the edema morphology and the ELM (external li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…According to the group of authors [14][15][16] there is a significant correlation between the average thickness of macular area (OCT data) and visual acuity in patients with diabetes and diabetic retinopathy in laser and/or intravitreal therapy over time. [17][18][19] However, other studies have shown no correlation or its presence in a moderate degree and there is still no consensus on this matter. 20 Yohannan et al, 21 report a correlation between a sensitivity of retina and photoreceptor state in patients with diabetic macular edema (DME).…”
Section: Discussionmentioning
confidence: 99%
“…According to the group of authors [14][15][16] there is a significant correlation between the average thickness of macular area (OCT data) and visual acuity in patients with diabetes and diabetic retinopathy in laser and/or intravitreal therapy over time. [17][18][19] However, other studies have shown no correlation or its presence in a moderate degree and there is still no consensus on this matter. 20 Yohannan et al, 21 report a correlation between a sensitivity of retina and photoreceptor state in patients with diabetic macular edema (DME).…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration with the growing literature regarding the EZ is how to objectively and consistently evaluate disruption. Few studies have analyzed the percentage disruption of each layer, few have classified the EZ disruption into less than or more than 200 microns, while others have merely comment on the integrity [ 42 , 43 , 44 , 45 ]. Considering all the evidence on the effect of outer retinal changes on OCT on visual outcome, it can be concluded that a visible sub-foveal loss of ellipsoid layer or ELM and the percentage disruption are definite poor visual prognostic indicators [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Objective Factorsmentioning
confidence: 99%
“…In patients with diabetes and diabetic retinopathy, single measurements of central foveal thickness using OCT were shown to correlate with visual acuity and to be a successful means of monitoring macular thickening before and after laser therapy 1 , 2 and/or intravitreous therapies. 3 5 However, other studies report conflicting results; some studies have shown no correlation while others have shown a moderate correlation, and this issue is still in discussion. 5 7 …”
Section: Diabetic Retinopathymentioning
confidence: 99%
“… 3 5 However, other studies report conflicting results; some studies have shown no correlation while others have shown a moderate correlation, and this issue is still in discussion. 5 7 …”
Section: Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation